Ganga: A Journey Down the Ganges River - Crandall Hollick Julian (Island Press, 2008)
The Ganges has always been more than just an ordinary river. For millions of Indians, she is also a goddess. According to popular belief, bathing in “Mother Ganga” dissolves all sins, drinking her waters cures illness, and dying on her banks ensures freedom from the cycle of death and rebirth.